Peningkatan Nilai Tambah Produk Pangan Lokal Melalui Pelatihan Pembuatan Bakso Dan Telur Asin Di Kelurahan Mokoau Kecamatan Kambu: Increasing the Added Value of Local Food Products Through Training in Meatball and Salted Egg Production in Mokoau Village, Kambu District - Saili, Takdir; Analuddin, La Ode; Santi, Nur; Badaruddin, Rusli; Hakim, Muh Haidir (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2025)
This community service activity aims to increase the added value of local food products through training in making meatballs and salted eggs in Mokoau Village, Kambu District, Kendari City. Local food ingredients such as beef and duck/chicken eggs are abundant, but their use is still limited to household consumption. The activity implementation method includes preparation, theoretical and practical training, and evaluation of training results. This activity was held from September to October 2025, involving 25 participants consisting of housewives and local micro, small, and medium enterprises (MSMEs). The results of the activity showed an increase in the participants' ability to process local food ingredients into products with higher economic value. The meatballs and salted eggs produced had good taste and potential to be developed as a home business. The training also increased public awareness of the importance of product hygiene and packaging. This activity contributed to community economic empowerment and strengthening local food security through food product diversification.